Isolation, purification and antimicrobial action of peptides produced by streptococcus salivarius isolated from Malaysian subjects / Abdelahhad Barbour - Barbour, Abdelahhad (2013)
Streptococcus salivarius is known to produce different bacteriocin-like inhibitory substances (BLIS). In this study six S. salivarius strains were isolated from different Malaysian subjects. The isolates were identified using morphological and biochemical characterization and 16S rDNA gene sequencing. Levansucrase enzyme was characterized from sucrose-enriched culture of strain S. salivarius YU10. BLIS production was investigated using simultaneous and deferred antagonism tests that showed YU10 and NU10 as the best BLIS-producing strains among the Malaysian isolates in this study. Strain HJEFF was the only S. salivarius isolate which produced a more limited quantity of BLIS in liquid medium. However, all other strains failed to produce any BLIS activity in liquid media. The distribution of salA, sboB and sivA genes encoding the production of salivaricin A, B and 9 was investigated in this study using BLIS producing strains NU10 and YU10. Strains NU10 and K12 (commercial probiotic) were the only strains that harboured the sboB structural gene. Both strains (NU10 and YU10) but not K12 harbored the sivA structural gene. Isolation of BLIS was done using acidic methanol extraction of the producer cells and freeze thaw extraction. BLIS-YU10 proved bacteriostatic while BLIS-NU10 was bactericidal. When added to different growth phases of sensitive bacteria, BLIS-NU10 reduced its growth significantly. BLIS-NU10 was purified from its crude form using different steps of initial purification namely ammonium sulphate precipitation, gel filtration, XAD-2 and solid phase extraction chromatography. BLIS-NU10 showed to be auto-regulated whereby it enhanced the production of the same molecule when added to NU10 culture. The induction ability was used to develop BLIS-production in liquid medium. BLIS-NU10 showed to be of cationic nature and it was iii purified using a cation exchange column. The cation exchange chromatography was performed using Fast Protein Liquid Chromatography system. Tris-ticine SDS page of the active fractions showed that BLIS-NU10 had a molecular weight of approximately 3,000 Da. The pure fraction was subjected to MALDI-TOF MS analysis. The only known salivaricin detected in BLIS-NU10 was salivaricin 9 (2560 Da). Other peptides where also detected in BLIS-NU10 with molecular weights of approximately 2,000 Da. BLIS-NU10 showed to have permeability activity towards selected target cells and showed to induce pore formation in the cytoplasmic membrane of targeted cells. The stability of BLIS-NU10 was also investigated in this study. BLIS-NU10 exhibited thermo-stability when exposed to 100oC for 30 minutes and retained biological activity when subjected to different pH values ranging from 2 to10. When treated with proteinase K or peptidase, BLIS-NU10 lost the antimicrobial activity. One major difficulty with strain NU10 was its erratic BLIS production. However, although strain NU10 harbors three different genes encoding known lantibiotics, analysis of pure BLIS-NU10 showed the presence of only lantibiotic salivaricin 9 in addition to other proline-rich peptides. The reason for the absence of salivaricin A and B in the purified BLIS-NU10 is still unknown and worthy of further investigation. Due to its uniqueness, strain NU10 can be further studied using whole genome sequencing approach to determine if this strain can be a potential probiotic.